2016
DOI: 10.1377/hlthaff.2016.0263
|View full text |Cite
|
Sign up to set email alerts
|

Medicare’s New Bundled Payment For Joint Replacement May Penalize Hospitals That Treat Medically Complex Patients

Abstract: The Centers for Medicare & Medicaid Services (CMS) recently implemented the Comprehensive Care for Joint Replacement (CJR) model. While many stakeholders are enthusiastic that the program will reduce spending for joint replacement, others are concerned that the program will unintentionally penalize hospitals that treat medically complex patients. This concern stems from the fact that the program may not include a mechanism to sufficiently account for patient complexity (i.e., risk adjustment). Using Medicare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…Indeed, a previous study has observed a statistically significant decrease in the average age and comorbidity of patients undergoing LEJR among academic centers during the risk‐bearing period of bundled payment for LEJR . The inclusion of HCC risk scores in LEJR reconciliation payments would lead to annual reductions in payments by as much as $146 360 for hospitals caring for the least medically complex patients and increases as large as $114 184 for hospitals with the most medically complex patients . These financial shifts in a cost‐neutral approach to reimbursement for CMS programs would serve to decrease the likelihood of adverse patient selection for higher cost patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a previous study has observed a statistically significant decrease in the average age and comorbidity of patients undergoing LEJR among academic centers during the risk‐bearing period of bundled payment for LEJR . The inclusion of HCC risk scores in LEJR reconciliation payments would lead to annual reductions in payments by as much as $146 360 for hospitals caring for the least medically complex patients and increases as large as $114 184 for hospitals with the most medically complex patients . These financial shifts in a cost‐neutral approach to reimbursement for CMS programs would serve to decrease the likelihood of adverse patient selection for higher cost patients.…”
Section: Discussionmentioning
confidence: 99%
“…The final CJR rule restricted adjustment to these three factors arguing that no standard risk adjustment methodology exists for LEJR patients, commercially available risk adjustment tools were constructed using patients not included within the CJR model, and traditionally employed risk adjustment methodologies such as the CMS‐Hierarchical Condition Category (CMS‐HCC) had not been validated in LEJR populations. Previous work has studied the net difference in hospital payment under the CJR model as currently implemented vs the inclusion of risk adjustment for average CMS‐HCC score aggregated to the hospital level: reconciliation payments would be reduced by $827 (95% CI, −$1368 to −$285) per episode for each standard deviation increase in a hospital's patient complexity, and risk adjustment could increase reconciliation payments for hospitals caring for more complex patients …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, CMS only plans to risk-adjust CJR payments for two scenarios that tend to be relatively expensive: fractures (i.e., nonelective cases) and DRG 469 which usually indicates a major medical complication [18••]. Research suggests that this will not adequately compensate providers for certain complex patient populations [61][62][63]. AAOS has voiced concerns about inadequate risk adjustment as well as the inclusion of TAA in the bundle.…”
Section: Cmmi and Bundled Paymentsmentioning
confidence: 99%
“…This is because the bundle assumes that care for all patients will be covered by the single bundle payment. However, a small subset of patients, termed "avalanche events" or "bundle busters," can have increased cost of care due to multiple-comorbidities or complications resulting in hospital re-admissions and this can cost between $100,000 to $150,000 per admission [5]. These patients, when mismanaged, fall outside the organization's process and capabilities.…”
Section: Introductionmentioning
confidence: 99%